Faktor risiko kematian akibat dengue di RSUP Dr. Sardjito Yogyakarta - Ruri Trisasri; Eggi Arguni; Riris Andono Ahmad (Berita Kedokteran Masyarakat (BKM), 2018)
Risk factors of death due to dengue hemorrhagic fever in a tertiary public teaching hospital of YogyakartaPurposeWe examined risk factors of dengue hemorrhagic fever death in Dr. Sardjito Hospital.MethodWe conducted a case control study from patient medical records and interviews with parents.ResultsWe found 29 deaths and 58 patients who survived. The probability of death among obese children was 6 times higher than non obese children and the probability of death in children with prolonged shock was 12 times higher than children without prolonged shock. Other variables were family occupation, family income, residential zones, transportation, treatment financing, accuracy of diagnosis in previous health facilities, and fluid resuscitation before being referred had no significant relationship with dengue mortality.ConclusionObesity and prolonged shock were risk factors of dengue hemorrhagic fever death in children. Improved education to parents about high risk of shock syndrome among patients is needed especially for obese children. Further studies related to social determinants in dengue hemorrhagic fever death are also necessary.